Defying decay: a strategy to enforce infrastructure standards in rural schools within the Eastern Cape, South Africa - Ndungane, Buyisiwe; Crafford, Gerrit; Moyo, Tirivavi (Frontiers in Built Environment, 2024)
The Eastern Cape Department of Education (ECDoE) in South Africa faces significant infrastructure challenges in rural schools, including inadequate funding, poor maintenance, and a shortage of essential facilities. These challenges hinder quality education provision and violate the Minimum Uniform Norms and Standards for Public School Infrastructure (MUNS-PSI) regulations. This study investigates these infrastructure challenges and proposes strategies to improve adherence to MUNS-PSI regulations. An interpretivist philosophy and inductive approach were adopted, focusing on a case study strategy. The study employed a mono-method qualitative approach, collecting data through semi-structured interviews with ten school managers and senior managers within the Chris Hani East District infrastructure delivery section. Purposive sampling was used to select participants, and thematic analysis was applied to the data. The findings revealed that the ECDoE lacks credible plans, sound systems, and effective leadership, resulting in poor governance and non-service delivery. Key challenges identified include the absence of a retention plan and a shortage of technological expertise. The study suggests forming a cross-functional group led by the head of the Department of Education to manage school infrastructure effectively. Training officials on technical skills related to the built environment and implementing the Infrastructure Delivery Management System are recommended. These strategies aim to enhance adherence to MUNS-PSI regulations, thereby improving the educational infrastructure and quality of education in the Eastern Cape.